Evaluation of Competency Standards for Vocational High School Graduates in the Era of Industrial Revolution 4.0 - Dwi Hastutiningsih, Arum; Ardiyanto, Ardi; Rina Miftakhi , Diah (Universitas Ahmad Dahlan, 2024)
In the rapidly evolving landscape of the Fourth Industrial Revolution, it is imperative to assess the readiness and competencies of vocational high school graduates. This evaluation is crucial to ensure that these graduates are equipped with the skills and knowledge necessary to meet the demands of modern industries. The study, which uses a descriptive qualitative method, evaluates Vocational High School graduates' competency standards in the Fourth Industrial Revolution era, particularly at State Vocational High Schools in Godean, Yogyakarta. The data analysis technique employed in this study involves qualitative methods, specifically thematic analysis, to identify and analyze critical themes and patterns related to the competencies and employment experiences of the graduates. Data were collected through interviews and observations of SMK graduates who have been employed or are currently seeking employment. The research findings indicate that the percentage of graduates who successfully obtain jobs related to their field of study or relevant is less than 40%. The main factor causing this is graduates' lack of interest or motivation to seek employment in Yogyakarta. Many graduates prefer to pursue job opportunities in other cities with lower competitiveness. Additionally, there is still a lack of willingness to develop themselves and improve the skills needed in the modern industry. It is crucial for graduates to understand the importance of continuous learning and self-development in the Fourth Industrial Revolution. In conclusion, organizing job fairs is recommended to facilitate graduates' entry into the industrial world by providing opportunities for direct interaction with industry representatives and access to diverse job vacancies. These efforts require close cooperation between local governments, educational institutions, and the industry to emphasize the importance of self-development and skills.